Efficient data collection from Open Modeling Interface (OpenMI) components - Bulatewicz, Tom; Andresen, Daniel (CSREA Press, 2013)
The management of output data from simulation models can be simplified in grid environments by automating and standardizing the way in which they are collected and stored. In the context of component-based computer models with well-defined input-output interfaces, generalpurpose data collector components can be linked to model components to retrieve output data and deliver them to online repositories via web services. We have developed a distributed data collector component that adheres to the Open Modeling Interface (OpenMI). The component buffers data to minimize the impact on a simulation’s runtime and shares the buffer across compute nodes for load-balancing and cooperative delivery of data to web services. The buffering capability resulted in minimal runtimes within a single simulation and reduced data delivery latencies for concurrently executing simulations across a cluster. In this paper we report on the design and performance of the component.
Keywords: OpenMI; Data; Web services; Modeling; Simulation